Determination of paroxetine in serum treated with simple pretreatment by pre‐column high‐performance liquid chromatography using 4‐(5, 6‐dimethoxy‐2‐phthalimidinyl)‐2‐methoxyphenylsulfonyl chloride as a fluorescent labeling reagent. (14th January 2013) - Inoue, Hirofumi; Harada, Takuya; Eto, Seiji; Nakashima, Ken; Ibusuki, Takuya; Kosha, Keiko; Date, Yuuko; Sanematsu, Emiko; Shinohara, Yoshitake; Takahashi, Kojiro; Yoshimura, Reiji; Nakamura, Jun; et al.
ABSTRACT: The therapeutic drug monitoring of paroxetine could be used to optimize the pharmacological treatment of depressed patients. A simple and sensitive high‐performance liquid chromatography procedure was developed for the determination of paroxetine in serum. After simple pretreatment of serum (50 μL) with acetonitrile and o ‐phthalaldehyde, paroxetine was derivatized with 4‐(5, 6‐dimethoxy‐2‐phthalimidinyl)‐2‐methoxyphenylsulfonyl chloride at 70°C for 20 min in borate buffer (0.1 mol/L, pH 8.0) to produce a fluorescent product. The derivative was separated on a reversed‐phase column at 40°C for stepwise elution with (A) acetic acid (10 mmol/L) and (B) acetonitrile. The flow rate was 1.0 mL/min. The fluorescence intensity was monitored at excitation and emission wavelengths of 320 and 400 nm, respectively. The within‐day and day‐to‐day relative standard deviations were 3.0–3.4 and 2.7–8.3%, respectively. The detection limit of paroxetine was 8.3 fmol at a signal‐to‐noise ratio of 3. As the proposed method that only requires a small quantity of serum (50 μL) is simple, sensitive and reproducible, it would be useful for clinical and biochemical research as well as drug monitoring. Copyright © 2013 John Wiley & Sons, Ltd.